Health Data Protection and Privacy in The Internet of Things Era: The New Legal Challenges in Indonesia - Nuzul Quraniati Rohmah (Leges Privatae, 2024)
This article addresses the absence of data protection regulations in Indonesia and the implications for personal data security, particularly in the context of the Internet of Things (IoT) and E-Health innovations within the health sector. Personal data, inherently sensitive, requires adequate protection to preserve individual privacy. Despite the benefits of IoT in healthcare, including increased efficiency and effectiveness, concerns arise regarding the security of patient health data. The lack of comprehensive regulations exacerbates the risk of data abuse or leakage by health providers or other parties. Drawing upon legal frameworks and recent cases of personal data violations, the article underscores the urgency for Indonesian governmental action to safeguard personal data, especially in the rapidly evolving landscape of IoT-enabled healthcare services.